Dynastic measures of inter-generational mobility with empirical evidence from Indonesia - Olivier Bargain; Maria C. Lo Bue; Flaviana Palmisano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We suggest a simple and flexible criterion to assess inter-generational mobility. It accommodates different types of outcomes (continuous outcomes such as potential earnings, or discrete ones such as education groups) and captures dynastic improvements of such outcomes at different points of the initial distribution. We provide dominance characterizations-for instance, on the relative progress made by women vs men-that are consistent with social preferences upon desirable patterns of mobility. We suggest an application for Indonesia. Exploiting IFLS data to match parents observed in 1993 to their children in 2014, we provide one of the rare intergenerational mobility analyses based on a long panel in the context of a poor country. Results indicate that mobility in terms of education and potential earnings were markedly to the advantage of women. A large part of the population was lifted out of illiteracy, possibly due to large-scale education and school construction reforms. However, our mobility index also shows that educational mobility was regressive and has, in turn, reduced the progressivity of the mobility in terms of potential earnings.
Keywords: J6; J62; O12; 330; inter-generational mobility; education; social welfare; Indonesia; gender